Unsaturated fatty acid‐induced non‐canonical autophagy: unusual? or unappreciated?. (11th March 2015) - Bankaitis, Vytas A
<x xml:space="preserve">Abstract</x> The breakdown of cellular components via autophagy is crucial for cellular homeostasis. In this issue of The EMBO Journal, Niso‐Santano et al (2015) report the important observation that feeding cells with saturated or unsaturated fatty acids triggers mechanistically distinct autophagic responses. Feeding cells saturated fatty acid induced the canonical, BECN1/PI3K‐dependent autophagy pathway. Conversely, the unsaturated fatty acid oleate triggered autophagic responses that were independent of the BECN1/PI3K complex, but that required a functional Golgi system.